A clinical decision support system to improve adequate dosing of gentamicin and vancomycin. (April 2019) - Pereboom, Marieke; Mulder, Inge J.; Verweij, Sjoerd L.; van der Hoeven, Ruud T.M.; Becker, Matthijs L.
Abstract: Objective: Gentamicin and vancomycin meet the criteria for measuring plasma concentrations during therapy. However, compliance with the accompanying guidelines remains low. The primary objective of this study was to determine whether the implementation of a clinical decision support system, which displays an alert if a plasma concentration should be measured and a daily reviewed patient list resulted in improved compliance. Materials and methods: This intervention study was performed at the Spaarne Gasthuis, Haarlem/Hoofddorp, the Netherlands. The authors included 261 treatments with either gentamicin or vancomycin intravenously for at least 48 h in the year before and after implementation of the clinical decision support system in May 2015. The authors analyzed whether plasma concentrations were measured sooner and more frequently after the implementation, and determined whether the time until the correct dosage, with adequate drug concentrations, was reduced after implementation. Results: Before implementation, plasma concentrations were measured within 72 h in 47% of the treatments. After implementation, this percentage increased to 80% (p < 0.01). After implementation, the time was significantly shorter until the correct dosage was given. Conclusion: The implementation of a clinical decision support system and a patient list resulted in improved compliance with the guidelines and optimized the treatment with gentamicin and vancomycin.